Assessing students’ mathematical reasoning in problem-based learning: a gender perspective - Romadhon, Nurul Isnaini; Amir, Mohammad Faizal; Wardana, Mahardika Darmawan Kusuma (Institute of Advanced Engineering and Science, 2024)
Mathematical reasoning (MR) in problem-solving is still relatively low, but students need it. Previous studies have shown that problem-based learning (PBL) can improve MR. Meanwhile, differences in MR are also influenced by gender. This study assesses MR quantitatively and qualitatively by reviewing gender differences when given PBL intervention. The research participants involved were fifth-grade primary students. The sampling techniques used were convenience and purposive sampling. This study design uses an explanatory sequential mixed method with quantitative data collection followed by qualitative data. Instruments like MR tests, interview guides, and questionnaires were used to collect data. Analysis techniques used for quantitative data are descriptive statistics, n-gain, and Wilcoxon signed-rank test, while qualitative data is thematic analysis. The study found that quantitatively, PBL significantly affects the MR of students with different gender perspectives. Meanwhile, qualitative findings in MR varied among students of different genders (masculine, feminine, and neutral) in the implication of PBL. Another finding is that students’ MR is inadequate in generalizing the statement. The study results provide comprehensive findings regarding the differences in MR of students with gender differences in the implications of PBL, which can contribute practical, theoretical, or methodological to teachers, practitioners, researchers, and scholarship.